A prospective study of concussions and health outcomes in high school football players - McGuine, T. A.; Pfaller, A.; Hetzel, S.; Broglio, S. P.; Hammer, E. (Journal of Athletic Training, 2020)
Context: Football is the most popular sport among US high school students and among the highest for sport-related concussion (SRC) incidence. Limited data detail how SRCs affect high school football players' psychosocial and health status beyond short-term injury recovery. Objective: To longitudinally assess how SRCs affected symptoms, depression, and health-related quality of life (HRQoL) in high school football players up to 12 months after SRC. Design: Prospective cohort study. Setting: Thirty-one Wisconsin high schools. Patients or Other Participants: A total of 1176 interscholastic football players (age = 16.0 ± 1.2 years). Main Outcome Measure(s): Participants completed the Post-concussion Symptom Scale (PCSS) from the Sport Concussion Assessment Tool 3 (SCAT3), Patient Health Questionnaire-9 (PHQ-9) for depression, and Pediatric Quality of Life Inventory 4.0 (PedsQL) for HRQoL at enrollment. Participants who sustained an SRC repeated each measure within 72 hours of their injury (onset) and at 7 days (D7), return to play (RTP), and 3 months (M3), 6 months (M6), and 12 months (M12) after SRC. Scores at each time point were compared with each participant's baseline using linear mixed models for repeated measures while controlling for age and previous SRC with participant as a random effect. Results: Sixty-two participants sustained an SRC. Participants reported a higher number of PCSS symptoms, greater symptom severity, and lower PedsQL physical summary scores at onset and D7. From RTP through M12, PCSS symptoms, PCSS severity scores, PedsQL total scores, physical summary, and psychosocial summary were unchanged or improved relative to baseline. The PHQ-9 scores were not higher than baseline at any post-SRC interval. Conclusions: High school football players in this study who sustained an SRC described no sustained adverse health outcomes (increased PCSS symptoms or symptom severity, increased depression symptoms, or lower HRQoL) after their RTP through M12 after injury.